A key to European species of Hyposoter Förster, 1869(Ichneumonidae: Campopleginae) with descriptions of 18 new species, and notes on all included species - Galsworthy, Anthony; Shaw, Mark R.; Haraldseide, Håkon (Zootaxa, 2023)
An identification key is presented to European species of Hyposoter falling morphologically within the definition of Townes (1970). Eighteen new species are described: Hyposoter aglyphus Galsworthy & Shaw sp. nov., H. albosignatus Galsworthy & Shaw sp. nov., H. castaneus Galsworthy & Shaw sp. nov., H. flavicoxa Galsworthy & Shaw sp. nov., H. flaviventer Galsworthy & Shaw sp. nov., H. heidiella Galsworthy & Haraldseide sp. nov., H. horstmanni Galsworthy & Shaw sp. nov., H. jubator Galsworthy & Shaw sp. nov., H. karmensis Galsworthy & Haraldseide sp. nov., H. monensis Galsworthy & Shaw sp. nov., H. morairae Galsworthy & Shaw sp. nov., H. naso Galsworthy & Shaw sp. nov., H. pechipogator Galsworthy & Shaw sp. nov., H. pseudodidymator Galsworthy & Shaw sp. nov., H. pseudovalidus Galsworthy & Shaw sp. nov., H. rivulator Galsworthy & Shaw sp. nov., H. ruficoxator Galsworthy & Shaw sp. nov., H. rufonigrator Galsworthy & Shaw sp. nov. Angitia alpicola Smits van Burgst, 1914 is transferred to Hyposoter comb. nov. H. carbonarius insulator Aubert, 1960 is raised to species level stat. nov. H. dubitatus (Holmgren, 1860) is returned to full species status from synonymy with H. sicarius (Gravenhorst, 1829) stat. rev. The following new synonymies are proposed: Limneria obscurella Holmgren, 1860 of Limneria neglecta Holmgren, 1860 syn. nov.; Anilasta berberatae Habermehl, 1922 of Campoplex seniculus Gravenhorst, 1829 syn. nov.; Hyposoter nigrior Aubert, 1993 of Anilasta tibialis Hedwig, 1938 syn. nov.; Rhythmonotus singularis Schmiedeknecht, 1909 of Campoplex tricolor Ratzeburg, 1844 syn. nov.; Hyposoter postcaedator Aubert, 1964 of Hyposoter alpicola Smits van Burgst, 1914 syn. nov. Lectotypes are designated for the following names: Hyposoter postcaedator Aubert, 1964; Hyposoter carbonarius insulator Aubert, 1960; Hyposoter rufovariatus meridionellator Aubert, 1965; Hyposoter praecaedator Aubert, 1963; Hyposoter rapacitor Aubert, 1971. Notes are provided on all included species.